"Theological Sophistry?" Does the Notion of Creation Need Revision?. Issue 3 (3rd July 2022) - Kopf, Simon Maria
ABSTRACT: The notion of creation is apparently up for debate again in the science and theology dialogue, after having been one of the major topics of agreement. At least since the Divine Action Project, the common consensus has been that general divine action, that is, divine creation and conservation, is relatively uncontroversial and broadly agreed upon, whereas special divine action, to wit, divine action that goes beyond creation and conservation, including some form of efficient causal particularity, is the subject of the controversy. In this article, I will respond to and reject five claims Joseph Hannon has recently advanced against this consensus and especially William Carroll's classical interpretation of creation ex nihilo, by which he attempts to show that Carroll grossly misrepresents Aquinas' account of creation: (1) creative divine action does not involve the giving of existence, but instead produces change; (2) creation is "making, " otherwise God cannot make matter; (3) Carroll's interpretation of creation amounts to Deism, since creation does not effect change in the material world; (4) this view rests on a confusion of ontological and causal dependence and hence (5) is to be rejected as "metaphysicalist" because on this view divine and creaturely causation operate on two different levels of reality.